Diurnal variation of the potassium layer in the upper atmosphere. Issue 9 (15th May 2015) - Feng, W.; Höffner, J.; Marsh, D. R.; Chipperfield, M. P.; Dawkins, E. C. M.; Viehl, T. P.; Plane, J. M. C.
Abstract Measurements of the diurnal cycle of potassium (K) atoms between 80 and 110 km have been made during October (for the years 2004–2011) using a Doppler lidar at Kühlungsborn, Germany (54.1°N, 11.7°E). A pronounced diurnal variation is observed in the K number density, which is explored by using a detailed description of the neutral and ionized chemistry of K in a three‐dimensional chemistry climate model. The model captures both the amplitude and phase of the diurnal and semidiurnal variability of the layer, although the peak diurnal amplitude around 90 km is overestimated. The model shows that the total potassium density (≈ K + K+ + KHCO3) exhibits little diurnal variation at each altitude, and the diurnal variations are largely driven by photochemical conversion between these reservoir species. In contrast, tidally driven vertical transport has a small effect at this midlatitude location, and diurnal fluctuations in temperature are of little significance because they are small and the chemistry of K is relatively temperature independent.